Perpètua de Cartago i Camar de Tunis. Sobre algunes fonts del Curial accessibles a Itàlia. - SOLER, ABEL (Scripta, 2016)
The scholars of the Curial have easily related the love of the African Camar with the love stories --also African-- of Eneas and Dido. However, they have not paid attention to the igure of the Roman martyr Perpetua of Carthage, a young scholar of the Eneida who was tied to a post and exposed to the lions, among other biographical aspects that could be linked to the character of Camar in the Curial. The revision of the Minutes of the martyrdom (versions A and B, released together) and the ictionalized Passio Perpetuae (3rd century) allow us to notice coincidences in the plot and intertextual connections with the chivalric novel of the 15th century. The fact that these sources were easily accessible in Italy (Milano, Naples) and unknown in the Iberian Peninsula reinforces the idea --generally accepted by the criticism-- of a Curial e Güelfa written in relation with the court in Naples of Alfonso the Magnanimous. The parodic treatment that the anonymous writer makes of the devotional sources also seems to be especially interesting to describe him intellectually and to interpret the work properly.